Extracurricular training as an effort to increase students' talents and interests - Hasyim, Mutahharah; Martawijaya, M. A.; Haris, Abdul; Mahir, Mahir; Taqwin, Muhammad (Borneo Novelty Publishing, 2025)
Extracurricular activities are activities to channel interests and talents for students at school. This extracurricular activity is very necessary in order to increase students' knowledge in the field of sports and help students form character according to their interests and talents. Therefore, in an effort to increase the motivation of students at SMP Negeri 4 Sendana which is located in North Tammedoro village, Tammerodo Sendana district, Majene district, South Sulawesi Province, the PkM team conducted a program of activities through sports training which included physical and technical exercises. The target of this program is all students of SMP Negeri 4 Sendana. The benefits resulting from this activity provide fun and positive activities, create media to channel students' interests and talents, and help improve achievements, especially in the field of sports.